1991
DOI: 10.1103/physrevc.43.716
|View full text |Cite
|
Sign up to set email alerts
|

Time scales for binary fragmentations of highly excited, fissile nuclei fromS32+

Abstract: Fission of ' Au, ' Th+838-MeV ' S projectiles was studied by measuring fragment coincident neutrons. Neutron energy spectra were decomposed into preequilibrium, prescission, and postscission contributions with a constrained moving source analysis. Excitation energies deduced from the transferred linear momentum are consistent with calculations applying the Boltzmann master equation, and with an energy balance based upon the experimental neutron multiplicities and charged particles from evaporation calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 60 publications
3
34
0
Order By: Relevance
“…In many experimental studies on heavy systems it is commonly found that if the temperature of the compound nucleus T CN is raised, the temperature at scission point T SC remains almost constant [1,10,27]. This supports the picture in which fission occurs after that the composite nucleus has cooled down until has reached an excitation energy of roughly 50-60 MeV, independently on the excitation energy of the initial compound nucleus.…”
Section: How To Probe a Temperature-dependent Viscositysupporting
confidence: 54%
“…In many experimental studies on heavy systems it is commonly found that if the temperature of the compound nucleus T CN is raised, the temperature at scission point T SC remains almost constant [1,10,27]. This supports the picture in which fission occurs after that the composite nucleus has cooled down until has reached an excitation energy of roughly 50-60 MeV, independently on the excitation energy of the initial compound nucleus.…”
Section: How To Probe a Temperature-dependent Viscositysupporting
confidence: 54%
“…The recoil velocity V of the composite system parallel to the direction of the beam was determined from the measured folding angle and fragment velocities of each event, following the procedure given in Ref. [20]. The ratio V /V CN, where V CN is the composite system velocity for full momentum transfer, was obtained as a function of fragment-mass ratio m R .…”
Section: Discussionmentioning
confidence: 99%
“…It contained two position-sensitive low-pressure multiwire chambers MWC of active size 61 x 61 mm 2 and two surface barrier detectors F2, F3 (thickness 170 #m, active area 700 mm z) in fixed positions in a planar geometry. Distances, angles and solid angles are given in Table 1 [10] in symmetric binary fragmentations and covered the range from 40% to 100% LMT for such events. Coincident heavy fragments observed with each one MWC and F detector on opposite sides of the beam focus on asymmetric fragmentations following high LMT.…”
Section: Methodsmentioning
confidence: 99%
“…p = 0.4-1.0), on a determination of neutron multiplicities by two different methods that allow comparison with those of [10], and on a discussion of effects broadening the LMT and thus the O12 distribution. To faciliate a comparison with the 4~ results from [2,8] we shall convert the LMT into an E~N scale by means of the massive transfer model.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation